2020
DOI: 10.1111/tbed.13831
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics and the influence of environmental variables on the prevalence of avian influenza virus in main wetlands in central Chile

Abstract: Although wild birds are considered the main reservoir of the influenza A virus (IAV) in nature, empirical investigations exploring the interaction between the IAV prevalence in these populations and environmental drivers remain scarce. Chile has a coastline of more than 4000 kilometres with hundreds of wetlands, which are important habitats for both resident and inter-hemispheric migratory species. The aim of this study was to characterize the temporal dynamics of IAV in main wetlands in central Chile and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 48 publications
1
25
2
Order By: Relevance
“…), show a positive relationship with H5N1 outbreak probabilities in wild birds in Europe. However, a relationship between bird richness and prevalence of avian influenza was not found previously in wetlands of central Chile (Ruiz et al 2021). Studies have shown that the black-headed gull (L. ridibundus) is highly susceptible to avian influenza in Europe, likely contributing to local transmission rather than longdistance spread due to their high mortality to H5N1 (Ramis et al 2014).…”
Section: Discussionmentioning
confidence: 85%
“…), show a positive relationship with H5N1 outbreak probabilities in wild birds in Europe. However, a relationship between bird richness and prevalence of avian influenza was not found previously in wetlands of central Chile (Ruiz et al 2021). Studies have shown that the black-headed gull (L. ridibundus) is highly susceptible to avian influenza in Europe, likely contributing to local transmission rather than longdistance spread due to their high mortality to H5N1 (Ramis et al 2014).…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, the probability of isolating a viable AIV sample from fecal biomaterial is, in general, lower than that from freshly taken tracheal and even cloacal swabs [47], so during the sampling of avian feces, special attention has to be paid to their quality in order to maximize the efficacy of live viral strain isolation. A study focusing on the dependence of AIV prevalence on environmental variables, such as bird quantity and species variety along with the temperature, rainfall, vegetation coverage, and water body size, has been performed in wetlands of Chile [49]. The results showed general prevalence of the virus in 4.28% of the droppings, with remarkable seasonal variations, peaking at 30% in summer months.…”
Section: Current Avian Influenza Virus Sampling Analysis and Quantification Methodologymentioning
confidence: 99%
“…where n = required sampling size, N = population size, ∝ = 1 -confidence level, and D = estimated minimum number of positive samples [49].…”
Section: Current Avian Influenza Virus Sampling Analysis and Quantification Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…HPAI A/H5Nx viruses in South America have only been detected in shorebirds and Charadriiformes hosts so far, likely due to passive detection systems. Active, longitudinal surveillance, especially in known AIV hotspots [7,8] should also focus on Anseriformes, given year long AIV circulation and genetic diversity in these species in Chile [8]. Further sequencing of A/H5Nx and non-A/H5 positive samples is critical to identify possible reassortment events with locally circulating AIV strains.…”
Section: Main Textmentioning
confidence: 99%